The periodontal ligament-periosteum sandwich hypothesis: A thought experiment on fenestrations and dehiscences - Huang, Greg J. (American journal of orthodontics and dentofacial orthopedics, 2025)
This article describes a hypothesis for bone recovery after iatrogenic dehiscences or fenestrations. When roots are moved out of the alveolar bone, the periodontal ligament and periosteum form a bilayer membrane (sandwich) over the exposed root. If the root is allowed to relapse back toward its original position, bone recovery will occur between the periodontal ligament and periosteum. •This article introduces a hypothesis regarding bone recovery after iatrogenic dehiscence or fenestration.•When roots are moved outside of bone, the periodontal ligament and periosteum become contiguous.•Recovery of bone may be highly related to roots relapsing back toward their original position.•This hypothesis needs clinical, radiographic, and histologic investigation to determine if it is valid.